SOSIALISASI DAN PENDAMPINGAN SISTEM PENGELOLAAN SAMPAH MENJADI KOMPOS SKALA SEKOLAH DI SD INPRES KANTISANG, TAMALANREA - Asiyanthi Tabran Lando; Abdul Nasser Arifin; Selintung Selintung; Kartika Sari; Ibrahim Djamaluddin; Muh. Akbar Caronge (LP2M Universitas Hasanuddin, 2019)
Socialisation and Accompaniment of The Waste Management System in Making School Scale Compost in SD Inpres Kantisang, Tamalanrea Abstract. At present, waste has become a severe problem that must be handled by the government and the community. Waste can damage the environment resulting in environmental pollution. Therefore, the proposal for the Community Service program is the socialisation and assistance of the waste management system in terms of making school scale compost, which is intended to convert organic waste into compost that is beneficial to plants and of economic value by using the Takakura composter. SD Inpres Kantisang, located in BTN Antara, Tamalanrea-Makassar became a partner or target audience in the proposed program. The problems faced by partners are: (1) not yet separated organic and inorganic waste in the school environment, (2) the presence of organic waste generated from the school environment and residents around the school that are not treated and utilized, (3) lack of knowledge of students in addressing the problem of organic waste, and (4) students do not yet know how to properly use and process organic waste, one of which is to process it into compost. The solution offered through this proposal is to conduct socialisation and assistance in the form of short training to teachers and students in making compost using the Takakura composter method from the waste generation in the school and surrounding areas. The method used in achieving these objectives is divided into five stages: the preliminary preparation, the program preparation, the implementation, the evaluation, and the sustainability of the program. The results of this activity are: (1) teachers and students of SD Inpres Kantisang have been able to separate organic and non-organic waste well, (2) an increase in the application of science and technology within the school environment, and (3) an improvement in governance value in the target audience.Keywords: waste, environment, compost, school, Takakura composterAbstrak. Saat ini sampah telah menjadi masalah serius yang harus ditangani oleh pemerintah dan masyarakat. Sampah dapat merusak lingkungan yang berakibat terjadinya pencemaran lingkungan. Oleh sebab itu, usulan program Pengabdian kepada Masyarakat ini adalah sosialisasi dan pendampingan system pengelolaaan sampah dalam hal pembuatan kompos skala sekolah, yang dimaksudkan untuk mengubah sampah organik menjadi pupuk kompos yang bermanfaat bagi tanaman dan bernilai ekonomi dengan menggunakan komposter Takakura. SD Inpres Kantisang yang berlokasi di BTN Antara, Tamalanrea-Makassar menjadi mitra atau khalayak sasaran dalam program ini. Masalah yang dihadapi mitra, adalah: (1) belum terpisahnya sampah organik dan anorganik di lingkungan sekolah, (2) adanya timbulansampah organik yang dihasilkan dari lingkungan sekolah dan warga sekitar sekolah yang tidak terolah dan termanfaatkan, (3) kurangnya pengetahuan para siswa dalam menyikapi masalah sampah organik, dan (4) para siswa belum mengetahui cara pemanfaatan dan pengolahan sampah organik dengan benar, yang salah satunya adalah dengan mengolahnya menjadi kompos. Solusi yang ditawarkan melalui usulan ini adalah dengan mengadakan sosialisasi dan pendampingan berupa pelatihan singkat kepada para guru dan siswa dalam membuat kompos dengan metode komposter Takakura dari timbulan sampah di lingkungan sekolah dan sekitarnya. Metode yang digunakan dalam pencapaian tujuan tersebut, terbagi atas: tahap persiapan, tahap penyusunan program, tahap pelaksanaan kegiatan, tahap evaluasi pelaksanaan program, dan keberlanjutan program ini. Hasil dari kegiatan ini, adalah: (1) para guru dan siswa-siswi SD Inpres Kantisang sudah dapat memisahkan sampah organik dan non-organik dengan baik, (2) terjadi peningkatan penerapan Iptek di dalam lingkungan sekolah, dan (3) adanya perbaikan tata nilai di khalayak sasaran.Kata Kunci: sampah, lingkungan, pupuk kompos, sekolah, komposter Takakura